Clinical Relevance of Subcentimetric Lymph Node Biopsy in the Diagnosis of Ocular Sarcoidosis. (3rd April 2022) - Bolletta, Elena; Mastrofilippo, Valentina; Invernizzi, Alessandro; Aldigeri, Raffaella; Spaggiari, Lucia; Besutti, Giulia; Borrelli, Roberto; Lococo, Filippo; Ricchetti, Tommaso; Rapicetta, Cristian; Cavazza, Alberto; Musci, Giovanni; et al.
ABSTRACT: Purpose: To evaluate the clinical relevance of subcentimetric lymph node biopsy via mediastinoscopy in patients with presumed ocular sarcoidosis (OS). Methods: Retrospective study of consecutive patients who underwent biopsy via mediastinoscopy for suspected OS. The biopsy outcomes and clinical features of patients with subcentimetric nodes and of those with lymph nodes >1 cm were compared. Results: A total of 67 patients with presumed OS were included. Forty-two patients (63%) had lymph nodes ≥1 cm in diameter, while 25(37%) showed subcentimetric lymph nodes. Biopsy was consistent with sarcoidosis in 83% of patients with lymph nodes ≥1 cm and in 76% of patients with subcentimetric lymph nodes (p = .60). Patients with OS who had subcentimetric lymph nodes had less lymphopenia (p = .01), lower lysozyme values (p = .03) and a longer diagnostic delay compared to those with larger lymph nodes. Conclusions: The biopsy of subcentimetric lymph nodes via mediastinoscopy may provide a histological diagnosis and reduce diagnostic delay.